Baseline Correction of Digital Accelerograms from Field Testing of a Seismically Isolated Building. Issue 2 (May 2018) - Athanasiou, Anastasia; Oliveto, Giuseppe; Ponzo, Felice
A three-story reinforced-concrete building in Augusta, Sicily, isolated at the base and designed according to the provisions of the latest Italian seismic regulations, was subjected to a series of push and sudden release tests in March 2013. During the tests, the displacements at the isolation level were measured along with the accelerations at each floor. The obtained records were then treated for the removal of low-frequency noise using a simple baseline-fitting scheme. The developed signal-processing scheme consists of defining the duration of the main event, removing the background noise, and using polynomial curves for the adjustment of the distorted baseline. The method does not require significant computational effort and accounts for initial and end conditions provided that these are known. Implementation of the method provides the adjusted response in terms of absolute and relative floor accelerations, velocities, and displacements, as well as interstory drifts.